Influence of Nanosilica Particle Addition on Mechanical and Water Retention Properties of Natural Flax- and Sisal-Based Hybrid Nanocomposites under NaOH Conditions - L. Natrayan; Dhinakaran Veeman; S. Baskara Sethupathy; S. Sekar; Pravin P. Patil; G. Velmurugan; Hulusew Ferede Mekonnen (Adsorption Science & Technology)
Organic filament-based lightweight materials are increasingly being used because of their high strength-to-weight ratio, recyclability, and low cost. The application of nanofillers in addition to natural fibres is a fascinating one. The main purpose of the current experimental investigation is to manufacture and estimate the mechanical material of nanocomposites. Natural fibres like flax and sisal are used as reinforcement; nanosilica particles act as fillers, and epoxy resin as a matrix. The composites were created using the Taguchi L9 orthogonal array and a hand lay-up technique. The mechanical and water retention behaviour of the hybrid composites is based on the following three parameters, each with three different levels: (i) adding different weight ratios of nanofiller (1.5, 3, and 4.5 wt%), (ii) weight ratio of reinforcements (20, 30, and 40 wt%), and (iii) duration of NaOCl conditions (2, 4, and 6 hours). Mechanical possessions like tension, bending, and impact were tested as per the ASTM standard. The tested composites show that 30 wt% reinforcement, 3 wt% nanosilica, and 4 hours of alkaline processing provide the best materials and aquatic preoccupation belongings. When compared to nanofiller composites, nanoparticle-filled composites have 17% evolution in tension, 22% upsurge in flexural strength, 13% in impact strength, and 36% increase in impact strength hygroscopic behaviour. Scanning electron microscopes were used to analyze the fractured structure of hybrid composites. Compared to 1.5 and 4.5 wt% of nanofiller, the 3 wt% of filler provides high interfacial adhesion to the hybrid composites. It helps the reinforcement and matrix to contact each other.